Bilateral Trading Processes, Pairwise Optimally, and Pareto Optimality - Feldman, A. M. (Review of Economic Studies, 1973)
Journal Article Bilateral Trading Processes, Pairwise Optimally, and Pareto Optimality Get access Allan M. Feldman Allan M. Feldman Brown University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 4, October 1973, Pages 463–473, https://doi.org/10.2307/2296581 Published: 01 October 1973